Parenting programme structure, potential barriers, and facilitators: a scoping review - Ramos, Ana (2022)
Becoming a parent is a challenging transition, and stress factors may arise. This scoping review aims to map, from the literature, the structure, potential barriers, and facilitators to be considered when conducting a parenting programme for parents of children up to 3 years old. It followed the JBI methodology and included studies with parents of children up to 3 years old (Participants), studies about parenting programme structure, its potential barriers, and facilitators (Concept) in the healthcare or community setting (Context). Qualitative and/or quantitative study designs and grey literature publications between 2016 and 2021 were eligible. The search was performed in three stages in CINAHL Plus with Full Text, MEDLINE with Full Text, and PubMed databases. It was also conducted in OpenGrey, ProQuest, Portuguese Open Access Scientific Repository, and Google Scholar. Fourteen articles were selected. The following aspects were identified regarding parenting programmes: benefits; structuring elements to be considered; facilitating factors and possible barriers to its development, and measurement instruments to assess the programme. Parenting programmes are important ways to contribute to a healthy, sustainable, and resilient society. It should be adapted to individuals, groups, and communities. They add value to parents, children, and society and should be carefully adapted to the group’s needs.